Peningkatan Pengetahuan Terhadap Kesehatan Tubuh, Gigi Dan Rongga Mulut Pada Komunitas Yoga - Farizka, Intan; Pratiwi, Deviyanti; Erawati, Jeti; Octarina; Ariesanti, Yessy; Tanaya, Namyera; Izah, Nurul; Anisa, Syafira (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Dental and oral health is an important part of overall body health. Lack of concern for body, dental and oral health is more due to the lack of proper understanding of the community in maintaining health in daily activities. Yoga is a form of exercise that is widely loved and associated with appreciation for body health and tranquility. Health education provided during yoga training is a form of effort to improve health by instilling concern for the importance of improving the quality of life with overall body health. This training was conducted on Saturday morning from 09.00-12.00, at health studio located at South Jakarta with 25 participants. The material was given after the yoga training in the form of presentations and questions and answers session. Evaluation of success was assessed from the analysis of the increase in pre-test and post-test results on 13 questions that showed the enthusiasm of the participants and an increase in understanding of body, dental and oral health. PKM activities that are tailored to the needs of partners have shown success in avoiding participant boredom. It is hoped that this activity can increase knowledge about body, dental and oral health.